A study of women's potential and empowerment for accelerating village development in Serdang Bedagai district, North Sumatera Province. Issue 5 (20th October 2021) - Kariono,; Badaruddin,; Humaizi,
ABSTRACT: The aim of this study is to identify and analyze the potential of women who could be empowered for rural development. To achieve these objectives, a combination of qualitative and quantitative approaches was used. This combination model is a dominant-less dominant design, where the qualitative data were obtained through in-depth interviews and observations, while the quantitative data were obtained through survey. The study was conducted in 5 villages in five Sub-districts in Serdang Bedagai District, North Sumatra Province, Indonesia. The sample in this study was 250 people. The results revealed that the women in the five villages studied had various potentials that could be developed and empowered, namely: (1) Potential Ability to Do Business in the Economy; (2) Potential Human Resource Capabilities; (3) Potential for Organizational Ability, and (4) Villages' Potential to Empower Women. These potentials would be developed if there was strong support from various parties such as, the government (Village, District, Province and Central Government), Non-Governmental Organizations (Civil Society), Universities, and Private Parties.